Isoquinoline Alkaloid Contents in Macleaya cordata Extracts and Their Acetylcholinesterase and Butyrylcholinesterase Inhibition - Tomasz Tuzimski; Anna Petruczynik; Małgorzata Szultka-Młyńska; Mateusz Sugajski; Bogusław Buszewski (Molecules, 2022)
An important strategy for treating neurodegenerative disorders is to maintain the levels of acetylcholine in the synaptic cleft by blocking the cholinesterases. Searching for new effective compounds with inhibited acetylcholinesterase and butyrylcholinesterase activity is one of the most significant challenges of the modern scientific research. The aim of this study was the optimization of the condition for cholinesterase activity determination by high-performance liquid chromatography coupled with diode array detector (HPLC-DAD) in terms of concentrations of enzymatic reaction mixture components, temperature of incubation, and incubation time. In vitro investigation of acetylcholinesterase and butyrylcholinesterase activity inhibition by some isoquinoline alkaloids and extracts obtained from the aerial part and roots of Macleaya cordata collected in May, July, and September. Acetylcholinesterase and butyrylcholinesterase activity inhibition of the extracts obtained from the plant had not been tested previously. The application of the HPLC method allowed eliminating absorption of interfering components, for example, alkaloids such as sanguinarine and berberine. The HPLC method was successfully applied for the evaluation of the acetylcholinesterase inhibitory activity in samples such as plant extracts, especially those containing colored components adsorbing at the same wavelength as the adsorption wavelength of 5-thio-2-nitro-benzoic acid, which is the product of the reaction between thiocholine (product of the hydrolysis of acetyl/butyrylthiocholine reaction) with Ellman’s reagent. Moreover, liquid chromatography coupled with a triple quadrupole mass spectrometer (LC–QqQ–ESI–MS/MS) analysis allowed evaluating the identification of relevant bioactive compounds in the obtained plant extracts. The investigated alkaloids, especially sanguinarine and chelerythrine, and all the Macleaya cordata extracts, especially the extract obtained from the aerial part collected in May, exhibited very high cholinesterase activity inhibition. HPLC-DAD was also applied for the kinetics study of the most active alkaloids sanguinarine and chelerythrine. Our investigations demonstrated that these plant extracts can be recommended for further in vivo experiments to confirm their cholinesterase inhibition activity.